A Mass-Preserving Characteristic Finite Difference Method for Miscible Displacement Problem (Advances in Applied Mathematics and Mechanics, 2023)
In this article, a new characteristic finite difference method is developed forsolving miscible displacement problem in porous media. The new method combinesthe characteristic technique with mass-preserving interpolation, not only keeps massbalance but also is of second-order accuracy both in time and space. Numerical resultsare presented to confirm the convergence and the accuracy in time and space.